Government COVID-19 stimulus package, SMEs' awareness, accessibility, and challenges in Cape Coast - Godson Kwame Amegayibor (Goodwood Publishing, 2023)
Purpose: This study analyzes the level of knowledge of the government's Covid-19 stimulus package among SMEs in the Cape Coast Metropolitan area. Research methodology: A quantitative and descriptive approach was employed. Using purposive sampling, 234 SMEs were selected. Data were collected through a structured questionnaire and analyzed using descriptive and inferential statistics via SPSS version 20. Results: The findings reveal that SMEs have a poor level of awareness and low access to the stimulus package. Additionally, political affiliation emerged as a significant barrier, along with other challenges in accessing support. Conclusion: Low awareness and limited access have hindered SMEs in Cape Coast from benefiting from the government’s Covid-19 stimulus package. Political factors and poor information flow were identified as key obstacles. More transparent and inclusive approaches are necessary to enhance support effectiveness during crises. Limitations: The study is limited in scope, focusing only on a single urban area. As the pandemic continues to affect business operations, broader research is recommended across wider regions. Contribution: The study reinforces the theoretical understanding that during a crisis like Covid-19, government intervention through financial support—explicit or implicit—is crucial to sustain the SME sector. It emphasizes the need for well-structured, inclusive policy implementation to enable SMEs to contribute effectively to national economic resilience.